Return to Work in Welder Underwent Total Knee Arthroplasty - Yohanes Edwin Jonatan; Aditya Pradana; Marsen Isbayuputra (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: Osteoarthritis is the most common musculoskeletal disorders found and after reached severe stage, total knee arthroplasty (TKA) should be considered. Welders are group of workers whose work dominated by kneeling or squatting position in long period and sometimes carrying heavy weights. Return to work (RTW) process in welder underwent TKA was varied by duration and activity limited post operation.Aim: to know whether welder underwent TKA could return to his original work.Methods: Searching literature for the evidence-based has been conducted with a clinical question through “PICO” method. Then we continued the searching using electronic databases: “PubMed”, “Cochrane Library”, “EMBASE”, and “Scopus”. The keyword is “osteoarthritis”, “total knee arthroplasty”, and “return to work” with all the synonyms combined with Boolean Operator. The inclusion criteria were blue collar worker or welder population, underwent TKA at most for one year, and full text article. While we excluded study in white collar worker or office worker population, partial knee arthroplasty procedure, and population age >65 years old.Results: From the three literatures obtained, we could learn about RTW duration in workers underwent TKA and what activities were limited after operation, and what the workers expectation after the procedure.Conclusion: Welder underwent TKA could return to work at least three months after the procedure was done, but modification in the workplace still need to be done.